2017
DOI: 10.1371/journal.pone.0186435
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cis-regulatory sequences reveals potential participation of lola and Deaf1 transcription factors in Anopheles gambiae innate immune response

Abstract: The innate immune response of Anopheles gambiae involves the transcriptional upregulation of effector genes. Therefore, the cis-regulatory sequences and their cognate binding factors play essential roles in the mosquito’s immune response. However, the genetic control of the mosquito’s innate immune response is not yet fully understood. To gain further insight on the elements, the factors and the potential mechanisms involved, an open chromatin profiling was carried out on A. gambiae-derived immune-responsive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…As a validation of our strategy to predict regulatory sites and TF binding, we reported the overlap between FAIRE-seq peaks determined in A. gambiae hemocytes in a previous study [27], with histone modifications ChIP-seq peaks in malaria-infected tissues. Even if the experimental conditions and cell types in the two studies are not comparable, we found 9136 MACS2 ChIP-seq peaks and 2690 diffReps regions (10% and 17% of the total, respectively) that intersected with FAIRE-seq peaks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a validation of our strategy to predict regulatory sites and TF binding, we reported the overlap between FAIRE-seq peaks determined in A. gambiae hemocytes in a previous study [27], with histone modifications ChIP-seq peaks in malaria-infected tissues. Even if the experimental conditions and cell types in the two studies are not comparable, we found 9136 MACS2 ChIP-seq peaks and 2690 diffReps regions (10% and 17% of the total, respectively) that intersected with FAIRE-seq peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Cis-regulatory elements are implicated in the control of gene expression because they contain specific DNA sequences that are binding sites for transcription factors and other chromatin remodelers, and often appear enriched in certain histone modifications. These elements are well mapped in Drosophila [48], but very few have been identified in mosquitoes [27, 49]. The analysis of differential ChIP-seq peaks located at promoters or gene bodies identified significant enrichment in binding sites that match consensus sequences of TFs previously described in Drosophila , including transcription factor deformed epidermal autoregulatory factor-1 (Deaf1) [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti and An. gambiae tissues (39,40). Among the differentially-expressed genes that seem to be regulated by differentially accessible CREs and that contain the above motifs, we found examples of immune-related genes (62), such as srpn6 or gam1, and genes that we identified in our previous study as Plasmodiumresponsive (42), such as the defensin def1.…”
Section: Discussionmentioning
confidence: 57%
“…aegypti and An. gambiae mosquitoes by FAIRE-seq (39)(40)(41). Chromatin accessibility at regulatory sites is generally of open CREs at introns respective to promoters, and vice versa: genes with higher intronic content contain more intronic THSs, and moreover, chromatin accessibility at these regions also correlates with higher accessibility of the cognate promoters and higher gene expression.…”
Section: Discussionmentioning
confidence: 99%